2021
DOI: 10.3390/medicina57050491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microcurrent Stimulation on Pain, Shoulder Function, and Grip Strength in Early Post-Operative Phase after Rotator Cuff Repair

Abstract: Background and Objectives: The purpose of this study was to investigate the effects of microcurrent stimulation on pain, shoulder function, and grip strength in patients with rotator cuff repair. Materials and Methods: This randomized single-blind controlled trial was conducted on inpatients of the rehabilitation department, and included 28 patients who underwent rotator cuff repair. Participants were randomly assigned to the experimental group (n = 14), treated with microcurrent stimulation, and the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The assessment measures were the following: (1) Patients’ sociodemographic characteristics and information related to RC pathology, rehabilitation measures, medicines and exercise intensity at home were recorded from the patient’s medical history. (2) Pain syndrome—intensity, severity, and nature of pain were evaluated by VAS scale [ 18 , 26 ] and McGill pain questionnaire [ 16 , 25 ]. (3) Shoulder motor function was evaluated using manual muscle strength testing (MMT) [ 13 , 15 , 16 ], shoulder active ROM [ 14 , 20 , 27 ], and dexterity of movements by Box&Block test [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment measures were the following: (1) Patients’ sociodemographic characteristics and information related to RC pathology, rehabilitation measures, medicines and exercise intensity at home were recorded from the patient’s medical history. (2) Pain syndrome—intensity, severity, and nature of pain were evaluated by VAS scale [ 18 , 26 ] and McGill pain questionnaire [ 16 , 25 ]. (3) Shoulder motor function was evaluated using manual muscle strength testing (MMT) [ 13 , 15 , 16 ], shoulder active ROM [ 14 , 20 , 27 ], and dexterity of movements by Box&Block test [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This consideration is vital due to the reduced motor function of the shoulder, arm and hand and increased disability observed as consequences of the long-term effect of pain, immobility and muscle stiffness, shoulder instability and limitation of daily life activities [ 22 , 33 ]. Many researchers assert a direct relationship between the patient’s psycho-emotional state, expectations, the presence of anxiety and the results of rehabilitation [ 18 , 34 ]. Sleep disorders are commonly observed in patients after RC repair, there is an increase in the quality of sleep with a parallel improvement in shoulder functions.…”
Section: Analysis Of Work Related To the Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…21 22 Several pieces of research have reported the beneficial effects of MCT, including pain relief, function improvement, wound healing and less irritation. [23][24][25][26][27] When integrated with traditional treatment, MCT has been shown to provide better outcomes than traditional treatment alone. 28 A recent clinical trial demonstrated the painreducing effect of MCT in knee OA.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…In vitro experiments have shown MCT accelerates the recovery of injured skeletal muscles 21 22. Several pieces of research have reported the beneficial effects of MCT, including pain relief, function improvement, wound healing and less irritation 23–27. When integrated with traditional treatment, MCT has been shown to provide better outcomes than traditional treatment alone 28.…”
Section: Introductionmentioning
confidence: 99%